Prevalence and correlates of bullying and victimization among school students in rural Egypt - Yasmine Samir Galal; Maha Emadeldin; Maha Abdelrahman Mwafy (SpringerOpen, 2019)
Abstract Objectives Knowledge on risk factors of bullying and victimization among school students is crucial for the implementation of preventive measures. This study was conducted to determine the prevalence and correlates of school bullying and victimization and their association with behavioral disorders among preparatory and secondary school students in rural Egypt. Study design Cross-sectional Methods A total of 476 students from two mixed public schools in rural Egypt (one preparatory and one secondary) were enrolled. A pretested self-administered questionnaire was used to collect sociodemographic characteristics and correlates of bullying and victimization including personal and social, family, school, and community factors. Frequency of bullying and victimization was measured using the short version aggression and victimization scale. The Strengths and Difficulties Questionnaire (SDQ) was used for screening behavioral problems. Results Prevalence of bullying behavior was high (77.8%) among the studied group, of those 9.5% were unique bullies, 10.5% were unique victims, and 57.8% were bully-victims. On multivariate logistic regression analysis, failure in previous scholastic years (OR = 11.1, 95% CI 1.1-101.4, P = 0.033), witnessing family members using weapons (OR = 6.1, 95% CI 1.1-34.0, P = 0.038), male gender (OR = 2.3, 95% CI 1.1-5.0, P = 0.027), and mothers' education (university or higher) (OR = 0.1, 95% CI 0.02-0.7, P = 0.017) remained the significant predictors for bullying. However, only having a drug addict friend (OR 2.5, 95% CI 1.1-5.4, P = 0.025) was the significant predictor for victimization. The independent predictors for being bully-victims in order of importance were exposure to physical violence in the street (OR = 5.1, 95% CI 1.2-22.7, P = 0.031), male gender (OR = 3.2, 95% CI 1.8-5.6, P < 0.001), witnessing fights (OR = 3.1, 95% CI 1.7-5.7, P < 0.001) and insulting words (OR = 2.5, 95% CI 1.3-4.7, P = 0.007) among family members, exposure to insulting words in the street (OR = 2.1, 95% CI 1.2-3.7, P = 0.010), watching violent movies (OR = 2.0, 95% CI 1.2-3.4, P = 0.008), and younger age (OR = 0.7, 95% CI 0.6-0.8, P < 0.001). The self-reported SDQ revealed that the conduct problems scale scored significantly higher among bully-victims (2.8 ± 1.7 vs. 2.3 ± 1.6, P = 0.004). Conclusions Prevalence of bullying behavior was high among rural adolescent school students. Establishment of a bullying prevention committee at school including all school personnel for addressing different factors associated with bullying behavior is recommended. Further follow-up and psychiatric assessment of students for predicting those prone to behavioral abnormalities are also recommended.